Law, Politics, and The Neutrality - Nafsiah, Maqfira Izzata (Semarang State University Undergraduate Law and Society Review, 2021)
Neutrality ASN (Aparatur Sipil Negara) is one of the most important part in the politics of this. But in fact during these many ASN that is not neutral because of weak laws that can ensnare ASN and because Bawaslu (Badan Pengawas Pemilu) and Panwaslu (Panitia Pengawas Pemilu) cannot reach the whole activity of the ASN leads to neutrality. To that end, the necessary optimal synergy between law enforcers in order to enforce the law firmly of the ASN that is not neutral in order to achieve a healthy democratic party and based on the principle of luberjurdil (langsung, bebas, rahasia, jujur, dan adil) which have mandated in the legislation.